2009
DOI: 10.1103/physrevb.80.075106
|View full text |Cite
|
Sign up to set email alerts
|

Large photoconductivity and light-induced recovery of the insulator-metal transition in ultrathinLa0.7Ce0.3MnO3δ

Abstract: Tetravalent-ion-doped lanthanum manganite films typically suffer from overoxygenation in the as-prepared state, which in turn leads to an effective hole doping instead of the nominal electron doping. This problem can be overcome by post-deposition annealing in a reducing atmosphere, which, however, suppresses the phase transition from an insulating to a metallic phase at the magnetic ordering temperature so that the films are insulating in the whole temperature range. In the present work, reduced La 0.7 Ce 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…To completely clarify which of the scenarios is the dominating one, a similar investigation of LCeMO on a nonphotoconductive substrate as well as a more extended study of the spectral dependence of the photoconductivity than in ref. 22 would be illuminative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To completely clarify which of the scenarios is the dominating one, a similar investigation of LCeMO on a nonphotoconductive substrate as well as a more extended study of the spectral dependence of the photoconductivity than in ref. 22 would be illuminative.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as discussed in our former XPS investigation 21 , oxygen reduction by heating in an ultrahigh-vacuum environment is a suitable way to drive the Mn valence towards 2 + /3+, which is, however, connected with a decisive resistance increase and the loss of an important functional property, namely the manganitetypical metal-insulator transition (MIT) 22 . As a fur- …”
Section: Introductionmentioning
confidence: 96%
“…[8,14,17], the transport measurements of the as-prepared samples were compared to the results of a 10-nm LCeMO thin film, referred to as sample A, which was already subject of these former studies.…”
Section: Methodsmentioning
confidence: 99%
“…[14] and refs. therein), while oxygen reduction by postdeposition annealing can indeed produce Mn valences below 3+, typically followed by the loss of the manganite-typical metal-insulator transition, producing films which are insulating across the whole temperature range [8]. A recent study by Middey et al [15] demonstrated that LCeMO thin films grown layer-by-layer with pulsed laser interval deposition showed already in the as-prepared state electron doping but remained insulating in the whole temperature range, too.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation